The use personal care products among students and their potential effects to the environment - Gopalakrishnan, Yashni; Ariffin, Siti Hidayah; Al Gheethi, Adel; Radin Mohamed, Radin Maya Saphira; Said, Shahrullneeza; Azizan, Mohd Sazwan; Nandong, Steven Suat; Ismail, Nurhasyima; Shamsul, Nurfasha Aqilah (Penerbit UTHM, 2020)
The presence and fate of pharmaceutical and personal care products (PPCPs) in the environment is undergoing increasing scrutiny. PPCPs entering the environment causes detrimental effects on environment and health. It contains diverse organic groups, such as antibiotics, hormones, antimicrobial agents, synthetic and musks. It raised significant concerns in recent years for their persistent input and potential threat to ecological environment and human health. A group of UTHM students have done a survey on the personal care products used by students in “Kolej Kediaman Bestari” UTHM, profile and their potential hazard to environment and health. From the survey, the mostly commonly used products by both male and female students have been identified.